An improvement to the existing measurement of poverty in Sri Lanka - Wimal, A.S.W.; Perera, S.K.; Thilakarathne, C.D. (University of Colombo, 2011)
Abstract Poverty is largely associated with demographic, socio-economic, cultural, environmental, health and psychological factors. The identification of the poor in the context of multidimensional nature of poverty is challenging and also a crucial aspect in any poverty alleviation program. Therefore the aim of this study is to develop an indicator, capable of capturing multidimensionality of poverty. 1. Introduction Analyses on poverty in Sri Lanka have been mainly carried out by Department of Census and Statistics (DCS) since mid eighties with the aim of combating poverty in the country. When the DCS announced the Official Poverty Line in 2004, the incidence of poverty computed using different criteria has produced different values in poverty, confusing the planners, policy makers and other data users [1]. These poverty lines were mainly based on income levels of individuals living in households. Poverty is multidisciplinary in nature. The early measures of poverty have not considered this feature. Therefore the existing measurement of poverty needs further strengthening. The specific objectives of the study are: ƒ To investigate the existing measurement of poverty in Sri Lanka ƒ To identify determinants of poverty ƒ To improve the existing measurement of poverty in Sri Lanka